Upaya Mengembangkan Kreativitas Belajar Siswa Kelas XI Melalui Layanan Bimbingan Belajar Di SMK Negeri 1 Lolowa’u - Luahambowo, Baspuri; Florina Laurence Zagoto, Sri (Program Studi Pendidikan Agama Islam, 2021)
This study aims to find out information about how to develop the learning creativity of class XI students through tutoring at SMK Negeri 1 Lolowa'u. According to the results of previous observations, efforts to develop learning creativity turned out to have a significant effect on tutoring. Based on these observations, the author tries to prove the truth through scientific research with the title: